Vector optimization problems and approximated vector optimization problems - Eugenia Duca; Dorel I. Duca (Journal of Numerical Analysis and Approximation Theory, 2010)
In this paper, a so-called approximated vector optimization problem associated to a vector optimization problem is considered. The equivalence between the efficient solutions of the approximated vector optimization problem and efficient solutions of the original optimization problem is established.